2021
DOI: 10.3390/ijerph18094741
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Phase Angle and Body Composition Fluctuation of Elite Ski Jumpers between Summer and Winter FIS Competitions

Abstract: (1) Background: The purpose of this study was to observe segmental phase angle (PhA) and body composition fluctuation of elite ski jumpers. (2) Methods: In the study, 12 professional ski jumpers took part. Body composition was estimated with segmental multi-frequency bioelectrical impedance analysis. Repeated ANOVA was used to check the parameters’ variability in time. The symmetry between the right and left side of the body was verified with the t-test for dependent samples. Pearson’s linear correlation coeff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 54 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…Only one recent study preceded our work in investigating side‐to‐side differences in BIA PhA among elite athletes. As such, this study by Ostachowska‐Gasior et al (Ostachowska‐Gasior, Piwowar, & Zajac, 2021) found no significant side‐to‐side differences in PhA with the Inbody S10 device at lower limb level in elite ski jumpers (17–29 years old). The differences could potentially be explained by the symmetrical nature of ski jumping, which might reduce the degree of lower limb asymmetry.…”
Section: Discussionmentioning
confidence: 58%
“…Only one recent study preceded our work in investigating side‐to‐side differences in BIA PhA among elite athletes. As such, this study by Ostachowska‐Gasior et al (Ostachowska‐Gasior, Piwowar, & Zajac, 2021) found no significant side‐to‐side differences in PhA with the Inbody S10 device at lower limb level in elite ski jumpers (17–29 years old). The differences could potentially be explained by the symmetrical nature of ski jumping, which might reduce the degree of lower limb asymmetry.…”
Section: Discussionmentioning
confidence: 58%
“…The increasingly common stand-on impedance devices are not only more convenient for the participant but also readily provide impedance measurements of the individual body segments not simply the whole body (hand to foot) measurements. This has provided the opportunity to measure phase angle of the separate body regions [32][33][34][35] more easily than with SFBIA lead devices (Fig. 7) [36].…”
Section: Measurement Of Phase Angle Some Practical Concernsmentioning
confidence: 99%